Tinjauan Makna dan Implementasi Adat Pemilihan Weton dalam Perkawinan Perspektif ‘Urf - aula, khodijah nurul; Azizah, Aisyatul (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2023)
Marriage is a series of sacred processions that cannot be separated from the provisions set by religious law. The implementation of marriage cannot be separated from the social culture of society which has been preserved for generations. One of the prohibitions or challenges in marriage that has developed in Javanese society is that the calculation of wehon is erratic or inappropriate. The aim of this research is to determine the meaning and implementation of the custom of selecting weton in marriage from a urf perspective. This research discusses the definition of wethon, the implementation of selecting wethon according to the opinions of scholars and according to urf. Apart from that, it also discusses urf analysis of the practice of calculating wethon in Sanankulon village. In this research, empirical methods are used, the data collection method in this research is interviews. The results of this research show that calculating the wethon is very ingrained in the community. This custom cannot be separated from people's lives. In fact, almost all the people of Sumber village, Sanankulon sub-district use calculating the wethon before marriage, in order to find a good day for marriage. Classification of the purpose of calculating the wethon that is done The prospective bride and groom's parents divide it into two, namely believing it is bad luck if it is not counted and only as a matter of caution or consultation. If you believe in bad luck then the action is considered shirk, but if it is just a consultation then it is not considered shirk.